2005
DOI: 10.1292/jvms.67.1067
|View full text |Cite
|
Sign up to set email alerts
|

A Neurological Disease with Spongy Degeneration in a Newborn Japanese Black Calf

Abstract: ABSTRACT. A Japanese Black calf, 3 day-old male, showed severe ataxia, lateral recumbency, and opisthotonos at the birth. Histopathological examinations revealed severe status spongiosis throughout the central nervous system. Numerous vacuoles within the neuropile varying in size and shape were observed in both formalin-fixed paraffin and cryostat sections. In the lesions, a limited number of spheroids and macrophages were observed within the myelin sheaths with very mild astrogliosis. These vacuoles were nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…We found that all data relating to calves were very similar between the wild-type and carrier cows, whereas data relating to the treatment of cows indicated that the frequency and cost of treatments were slightly higher in the carrier cows than in the wild-type cows, although differences between the two groups were not significant. [8,9] and maple syrup urine disease (OMIA 000627) [6]. Collectively, these genetic disorders are assumed to have a substantial economic impact on the JB cattle industry; however, the details have yet to be evaluated.…”
Section: Reproductive and Developmental Statusmentioning
confidence: 99%
“…We found that all data relating to calves were very similar between the wild-type and carrier cows, whereas data relating to the treatment of cows indicated that the frequency and cost of treatments were slightly higher in the carrier cows than in the wild-type cows, although differences between the two groups were not significant. [8,9] and maple syrup urine disease (OMIA 000627) [6]. Collectively, these genetic disorders are assumed to have a substantial economic impact on the JB cattle industry; however, the details have yet to be evaluated.…”
Section: Reproductive and Developmental Statusmentioning
confidence: 99%